Closing Achievement Gaps Through Preschool-to-Third-Grade Programs - Temple, Judy A.; Ou, Suh-Ruu; Reynolds, Arthur J. (Frontiers in Education, 2022)
Achievement gaps by family income, race, and ethnicity have persisted for decades. Yet only in recent years has this major social problem become a national priority in the U.S. and many other countries as concern rises over growing economic inequalities. In this paper, we document gaps in school readiness and achievement in the U.S. and how they adversely affect the life course development of children and families from underrepresented groups. We emphasize the promising role of preschool-to-3rd grade (P-3) programs to reduce a variety of achievement gaps through comprehensive strategies that enrich educational and family experiences during most of the first decade of life. Implementation of the core elements of effective learning experiences, collaborative leadership, aligned curriculum, parent involvement and engagement, professional development, and continuity and stability in the Child-Parent Center Program have shown relatively strong and sustained effects on school achievement, especially for Black children growing up in urban poverty. This evidence from the Chicago Longitudinal Study and other projects suggests that broader scale up of truly comprehensive approaches that begin early, continue through most of the first decade, and are multilevel in scope can make a bigger difference than many existing strategies in reducing achievement gaps and their persistence.